Relationship of Temporomandibular Joint Disorders and Psychological Distress in Young Adults - Hanin, Isya; Putri, Pramudita Wiyani (Dentistry Faculty, 2023)
Background: Temporomandibular disorders (TMD) relate to dysfunctions that impact the temporomandibular joint (TMJ), masticatory muscles, and connected structures. Psychological well-being can be among the various factors that TMD affects. Prior studies conducted in different countries have demonstrated a correlation between TMD symptoms and psychological distress in young adults. However, research on this topic is limited in Indonesia. Objective: To assess the association of symptoms of temporomandibular joint disorder and psychological stress in young adults. Materials and Methods: This research employed an analytical cross-sectional design and involved 354 participants (141 males and 213 females) aged 19-21 from Kampus A of Universitas Trisakti. The subjects' general characteristics, including gender, age, and ethnicity, were described. The data were gathered through two types of questionnaires: DC/TMD axis I (Symptom Questionnaire) and axis II (Patient Health Questionaire-PHQ-4), and were analyzed using the Spearman correlation test administered through Google Form. Result: The study's findings revealed that 141 participants (39.8%) were male, while 213 (60.2%) were female. Among the research subjects, 91 individuals - 32 males and 59 females - experienced the most discomfort in the pain category, with the mean PHQ-4 score for pain being the highest at 4.68. The bivariate analysis demonstrated a moderate correlation coefficient value (r = 0.401) and a significant relationship (p 0.05) between temporomandibular disorders (TMD) in the pain category and psychological distress. The prevalence of TMD was 39.8% in males and 60.2% in females. Conclusions: TMD is a common problem among young adults aged 19-21 years, and pain associated with TMD can lead to psychological distress in this age group.